PENGARUH KUAT TEKAN BETON DENGAN MENGGUNAKAN LIMBAH SERBUK BESI SEBAGAI ADMIXTURE AGREGAT HALUS - Subaidillah Fansuri; Anita Intan Nura Diana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
This study aims to determine the effect of the addition of iron powder waste as fine aggregate admixture to concrete compressive strength and to find out the optimum compressive strength of concrete after adding iron powder waste as fine aggregate admixture. Making concrete using iron powder is expected to be able to utilize iron powder waste that is not used anymore. Research results show that there is a significant influence with the addition of iron powder, but the addition of iron powder that is too excessive can also reduce the strength of the concrete itself. Good use of iron powder is at a variation of 10% - 30% with an optimum characteristic compressive strength of 21.42 N / mm2 and an effect of 26% - 60%.